Textiles impregnated with antimicrobial substances in healthcare services: systematic review - Schneider, Guilherme; Vieira, Leticia Genova; Carvalho, Herica Emilia Félix de; Sousa, Álvaro Francisco Lopes de; Watanabe, Evandro; Andrade, Denise de; Silveira, Renata Cristina de Campos Pereira (Frontiers in Public Health, 2023)
Background Antimicrobial textiles have proved to be a promising biosafety strategy. Thus, the current study was focused on identifying which antimicrobial substances impregnated in textiles used in healthcare services confer efficacy in reducing the microbial load present in these textiles and/or the Healthcare-Associated Infection (HAI) rates, when compared to conventional textiles. Methods A systematic review of intervention studies using MEDLINE via the PubMed portal, EMBASE, CINAHL, Web of Science, Scopus, Google Scholar and medRxiv. The studies identified were selected according to eligibility criteria and submitted to data extraction and methodological quality evaluation through Joanna Briggs Institute specific tools. The outcomes were synthesized qualitatively. Results 23 studies were selected to comprise the final sample, in which antimicrobial textiles were used by hospitalized patients, by health professionals during work shifts and in inanimate healthcare environments. Conclusions Copper, silver, zinc oxide, titanium and silver-doped titanium impregnated in textiles used by patients confer efficacy in reducing the microbial load of these textiles and/or the HAI rates. Quaternary ammonium, chlorhexidine, silver and copper together, quaternary ammonium, alcohols and isothiazolone derivatives together, chitosan and dimethylol dimethyl hydantoin together, all impregnated in textiles used by health professionals confer efficacy in reducing the microbial load of these textiles. Quaternary ammonium impregnated in textiles used in inanimate healthcare environments confers efficacy in reducing the microbial load of these textiles.